If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 2x = -32 + 12x Solving -16 + 2x = -32 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -16 + 2x + -12x = -32 + 12x + -12x Combine like terms: 2x + -12x = -10x -16 + -10x = -32 + 12x + -12x Combine like terms: 12x + -12x = 0 -16 + -10x = -32 + 0 -16 + -10x = -32 Add '16' to each side of the equation. -16 + 16 + -10x = -32 + 16 Combine like terms: -16 + 16 = 0 0 + -10x = -32 + 16 -10x = -32 + 16 Combine like terms: -32 + 16 = -16 -10x = -16 Divide each side by '-10'. x = 1.6 Simplifying x = 1.6
| 26+9n=264 | | x^2=100-10x | | 5(4+x)=6+3x | | 7(2-3a)=3(5a-1) | | x(3x+2)=1496 | | 3x+2y=12fory | | t^2+2t-14=0 | | 3x+8=-70-10 | | -2.8(x+4.9)=8.2 | | 8s^2-6s=2s | | 3(x+4)+2=5 | | 5z-3=1 | | 10x^2=100(10-x) | | 9x^2=-36 | | 52-3x=12-8x | | 9x-(2x-5)=4x+11 | | 8-2(4-x)=2x+5-3 | | 5p^2=12-10p | | 3(-6x+9)10x=1 | | 3m-10=25-4m | | 7(7-x)=133 | | 6x+8=-40-2x | | 3x^2-45x=-168 | | 2x-5y-6z= | | 4.4x-7.8x=21.08 | | x+x+1+x+2+x=192 | | (.25)4y=5(.25) | | 2x+14=-11-3x | | 3x+2y=12y | | 15+g=27 | | 7y-11-10y+3=7 | | -1+49x=21x+43 |